HUBUNGAN LINGKUNGAN KERJA FISIK TERHADAP STRES KERJA PERAWAT DI RUMAH SAKIT JIWA PROVINSI JAWA BARAT - Hayatunnufus Putrialif (2023)
The healthcare industry has one of the highest rates of occupational stress. A less favorable physical work environment is one of the reasons that might induce stress in nurses. The study's goal is to examine the association between the physical work environment and the level of job stress experienced by nurses at West Java Provincial Mental Hospital. A cross-sectional design and simple random sampling were used in the observational analytic approach. Male nurses made up 47 percent of the responses. The Fisher test was used to assess the data in univariate and bivariate analyses. The findings revealed that 24 nurses (51.1%) experienced light stress and 41 nurses (87.2%) thought the physical work environment was conducive, with a p-value of 1.000 and an OR of 0.952. There was not a substantial connection between the physical working environment and nurses' job stress. It is suggested that the hospital can maximize the procurement of air conditioners in each room because they are still needed when the air is not friendly so as not to disturb nurses and other workers while working. It is also hoped that hospitals can periodically evaluate the workload given to match the ability of nurses and that the hospital can also consider adding human resources if the evaluation results indicate that it is necessary.